Optimum Medium for Lipase Production by Lipolytic Filamentous Fungi Isolated from Kendari Landfill Soil - Nur Rayani; Miftahul Ilmi (ASEAN Journal on Science and Technology for Development, 2021)
Lipase produced by Aspergillus is widely known and used in many industrial sectors. In a previous study, three lipolytic filamentous fungi were isolated from Kendari (Southeast Sulawesi, Indonesia) landfill soil and identified as Aspergillus niger KE1, Aspergillus terreus KC1, and Aspergillus fumigatus KE6. However, the optimization of these isolates has not been reported. In this study, statistical optimization was selected because it is more effective, efficient, economical, and robust in achieving results, and the possibility of analyzing the interaction effects among factors. Three lipolytic isolates were screened in the initial medium to obtain the highest lipolytic isolate, which was used in the medium optimization process. Optimization was performed using the series experimental design of Taguchi and RSM. Optimization successfully obtained the optimum medium with the reduction of the medium component from the previously reported medium. Aspergillus niger KE1 was the selected isolate with the highest lipase productivity after 72 h in the initial medium. The significant factors affecting lipase production were peptone, olive oil, glucose, and MgSO4 .7H2O. The model equation obtained was Y = 1043 ? 228 A + 300 B ? 19803 C + 99 A*A + 5720 B*B + 292855 C*C ? 979 A*B + 6563 A*C ? 56338 B*C. This model successfully predicted the lipase productivity with an R2 of 96.9%. The optimized medium was composed of 2% peptone, 0.1% olive oil, 0.5% glucose, and 0.075% MgSO4 .7H2O. Using the medium, lipase productivity increases 4.7-fold. Our results suggest that A. niger KE1 is a potential lipase source which catalyses the esterification reaction. Further research is needed to purify and characterize the lipase enzyme of this isolate.